Beauveria bassiana Culturing and Harvesting for Bioassays With House Flies. Issue 6 (2nd November 2020) - Johnson, Dana M; White, Roxie L; Pereira, Roberto M; Geden, Christopher J
Abstract: The entomopathogenic fungus Beauveria bassiana (Balsamo) Vuillemin (Hypocreales: Cordycipitaceae) has been widely studied against a wide range of arthropod pests, including many of medical and veterinary importance. New investigators must sort through a wide array of published methods for the production, harvest, storage, and bioassay methods for this pathogen. Simplified methods for production of conidia using Sabouraud dextrose agar with yeast (SDYA) plates and two conidial harvesting methods are described. Dry harvesting yields conidia that are ready to incorporate into dusts and food baits, but the fungal product includes mycelial debris that can hamper quantification and introduces variable amounts of unwanted bulk. Wet harvesting with filtration produces a cleaner product that is immediately ready for testing in liquid formulations. Examples of bioassays with house flies are presented that include conidia applied topically to the dorsal thorax for dose–mortality assays and conidial suspensions applied to filter paper disks for concentration mortality assays.